Does dual oocyte retrieval with continuous FSH administration increase the number of mature oocytes in low responders? An open-label randomized controlled trial - Boudry, L; Mateizel, I; Wouters, K; Papaleo, E; Mackens, S; De Vos, M; Racca, A; Adriaenssens, T; Tournaye, H; Blockeel, C (Human reproduction (Oxford), 2024)
Is there an increase in the total number of metaphase II (MII) oocytes between a conventional ovarian stimulation (OS) and a double uninterrupted stimulation? There is no increase in the total number of MII oocytes when comparing one conventional OS to a continuous stimulation with double oocyte aspiration. Based on the concept of multiple follicular waves, the combination of two stimulations in the same ovarian cycle has gained interest in patients with a low ovarian reserve. This so-called dual stimulation approach is usually characterized by a discontinuation of FSH administration for ∼5 days and appears to have a favourable impact on the number of retrieved oocytes without affecting the embryo quality or ploidy status. The outcomes of dual uninterrupted OS have not yet been studied. This was an open-label randomized controlled trial (RCT) with superiority design, performed in a single tertiary centre. Subjects were randomized with a 1:1 allocation into two groups between October 2019 and September 2021. All patients underwent a conventional stimulation with recombinant FSH. When two or more follicles of 17 mm were present, the final inclusion criterion was assessed; randomization occurred only in the presence of ≤9 follicles of ≥11 mm. In Group A, ovulation was triggered with hCG, and oocyte retrieval (OR) was performed 34-36 h later, followed by a fresh single or double embryo transfer (SET or DET) on Day 3/5. In Group B, ovulation was triggered with GnRH agonist, followed by another OS, without discontinuation of the FSH administration. In the presence of one or more follicles of ≥17 mm, the second stimulation was completed with hCG. A freeze-all strategy (Day 3/5) was applied for both retrievals, followed by transfer of one or two embryos in an artificially prepared frozen-thawed cycle. In the absence of one or more follicles of ≥17 mm after 13 additional days of stimulation, the second cycle was cancelled. All ORs were executed by a senior fertility specialist who was blinded for the first treatment, and all follicles >10 mm were aspirated, according to routine clinical practice. The primary outcome was the total number of MII oocytes. Patients were followed up until all embryos were transferred, or until live birth was achieved. Other secondary outcomes included the number of cumulus-oocyte complexes (COCs), the number of good quality embryos (Day 3/5), the ongoing pregnancy rate, and gonadotropin consumption. Patients between 25 and 40 years old, with an anti-Müllerian hormone level of ≤1.5 ng/ml, antral follicle count of ≤6, or ≤5 oocytes after a previous stimulation, were included. At the start, 70 patients were eligible for participation in the trial, of whom 48 patients fulfilled the final inclusion criterium and were randomized. After drop-out of two patients, 23 patients were randomized to a single round of OS (Group A), and 23 patients were randomized to two uninterrupted rounds of OS (Group B). Baseline characteristics were similar between both groups. The cumulative number of COCs and MII oocytes after completion of the second OR was similar in Group A and Group B [5.3 ± 2.7 versus 5.3 ± 3.0 (P = 0.95); 4.1 ± 2.4 versus 4.3 ± 2.7 (P = 0.77)]. Likewise, a comparable number of excellent and good quality embryos was available on Day 3 (3.0 ± 2.0 versus 2.7 ± 2.0; P = 0.63). In Group B, the cancellation rate due to insufficient response to the second round of stimulation was 39.1% (9/23). When focusing on the first stimulation in both groups, there were no significant differences regarding basal FSH, gonadotropin consumption, and the number of preovulatory follicles. After the first OR, the mean number of COC and MII oocytes was significantly higher in Group A (who had hCG triggering), compared to Group B (who had GnRH agonist triggering) [5.3 ± 2.7 versus 3.3 ± 2.2; difference 95% CI (0.54 to 3.45), P = 0.004 and 4.1 ± 2.4 versus 3.0 ± 2.2; difference 95% CI (-0.15 to 2.6), P = 0.05, respectively]. Likewise, the number of excellent and good quality embryos on Day 3 was significantly higher (3.0 ± 2.0 versus 1.9 ± 1.7; P = 0.02) in Group A. This study was powered to demonstrate superiority for the number of MII oocytes after dual stimulation. Investigating the impact of dual stimulation on pregnancy rates would have required a larger sample size. Furthermore, the heterogeneity in embryo vitrification and transfer policies precluded a correct comparison of embryologic outcomes between both groups. This is the first RCT investigating the role of continuous stimulation with double aspiration in low responders. Our results show no statistically significant differences in the cumulative number of MII oocytes between one conventional stimulation with fresh ET and two consecutive stimulations with a freeze-only approach. Furthermore, the observed suboptimal oocyte yield after agonist ovulation triggering in low responders in the dual uninterrupted OS group is a reason for concern and further scrutiny, given that previous RCTs have shown similar outcomes in normal and high responders after hCG and GnRH agonist triggers. This work was supported in part by a research grant from Organon. H.T. received honoraria for lectures and presentations from Abbott, Cooper Surgical, Gedeon-Richter, Cook, Goodlife, and Ferring. L.B. received fees for lectures from Merck & Organon and support for attending ESHRE 2023. M.D.V. reports fees for lectures from Ferring, Merck, Organon, IBSA, Gedeon Richter, and Cooper Surgical and support for attending ASRM 2023. S.M. received honoraria for lectures and presentations from Abbott, Cooper Surgical, Gedeon-Richter, IBSA, and Merck. C.B. was on the Advisory board and received consulting fees from Theramex and received honoraria for lectures and presentations from Abbott, Ferring, Gedeon-Richter, IBSA, and Merck. NCT03846544. 19 February 2019. 28 October 2019.